Anticancer Effects of Wild Mountain Mentha longifolia Extract in Adrenocortical Tumor Cell Models - Patti, Felicia; Palmioli, Alessandro; Vitalini, Sara; Bertazza, Loris; Redaelli, Marco; Zorzan, Maira; Rubin, Beatrice; Mian, Caterina; Bertolini, Cristina; Iacobone, Maurizio; Armanini, Decio; Barollo, Susi; et al. (Frontiers in Pharmacology, 2020)
Mint (Mentha longifolia (L.) Hudson) is an aromatic plant that belongs to Lamiaceae family. It is traditionally used as herbal tea in Europe, Australia and North Africa and shows numerous pharmacological effects, such as spasmolytic, antioxidant, antimicrobial and anti-hemolytic. Recently its antiproliferative role has been suggested in a small number of tumor cell models, but no data are available on adrenocortical carcinoma, a malignancy with a survival rate at 5 years of 20-30% which frequently metastasize. This work aimed to study the effects of Mentha longifolia L. crude extract (ME) on 2 adrenocortical tumor cell models (H295R and SW13 cells). Chemical composition of ME was assessed by gas-chromatography/mass spectrometry analysis and total polyphenol content, as well as antiradical potential (DPPH• and ABTS∙+ assays) was evaluated. Brine shrimp lethality assay showed ME effects at >0.5 µg/µl. Cell viability and vitality were determined by MTT, SRB and trypan blue assays in H295R and SW13 cells. The anti-proliferative effects of ME were more evident in SW13 cells at 72h. Combination of ME with mitotane (approved drug for adrenocortical carcinoma) seemed not to reinforce the efficacy of the herb. As control, human fibroblasts were treated with ME with no effect on cell viability. Clonogenic assay was concordant with previous cell viability tests, while Wright staining demonstrated the presence of both necrotic and apoptotic cells. Cell cycle analysis showed a strong increase in subG0/G1 phase, related to cell death. The crude methanolic extract of wild mountain mint possesses antiradical and antioxidant properties and can decrease cell viability, vitality and survival of adrenocortical tumor cell models, in particular of SW13 cells. These data show the potential anticancer effects of ME, still more work is needed to corroborate these findings.